MAXIMIZING EMPLOYEE TURNOVER AS A STRATEGIC APPROACH TO EFFECTIVE MANAGEMENT: A STUDY OF SELECTED HOSPITALITY FIRMS IN OWERRI - DIALOKE, DR. IKECHUKWU; CHIMA, ANYANWU, PASCHAL (IJRDO - Journal of Applied Management Science, 2017)
this study focused on examining employee turnover as a strategic approach to management effectiveness. In conducting the study, descriptive survey approach was adopted and data was generated from a five point likert scale. The study covered a population of sixty (60) managers and supervisors of eleven (11) hospitality firms within the Owerri metropolis. Because of the smallness of the data, the entire population was used as its sample; however, out of the 60 questionnaires distributed, only 48 were correctly filled and returned; thereby given a questionnaire return rate of 80%. The data gathered was analyzed with the kruskawalis (H) test. This study haven surveyed literatures and conducted empirical inquiry came to the conclusion that employees turnover can be of both strategic benefit and challenge to management effectiveness. Following the findings and conclusion above, the study recommends that for turnover to yield desired positive result as a tool to enhancing management effectiveness, the followings should be considered; where it is needful to embark on involuntary turnover (disengagement), it must be done in phases in other to give room for the organizational memory to be passed on successfully to the new employee and that firms should endeavor avoid building the business capabilities around one personnel, rather it should be spread across board through open communication and participative management style. This will ensure that when voluntary employee turnover occurs; the firm can overcome the shock by effectively replacing him through internal processes. This will also help to bridge leadership and succession gaps